Implementasi Gerakan Anti Korupsi sebagai Upaya Pencegahan Korupsi pada Lembaga Anti Korupsi di Propinsi Jawa Timur - Emmilia Rusdiana; Nurul Hikmah (Faculty of Law Hang Tuah University, 2020)
The anti-corruption movement introduces the publik that prevention efforts are better than efforts to eradicate corruption itself. This case has been conducted by an anti-corruption activist representing the community. The purpose of this research is to know the experience and understanding in supporting and realizing the anti-corruption movement as an effort to prevent corruption in East Java society. This type of research is sociological juridical and analyzed qualitatively. The results of the discussion showed that Malang Corruption Watch (MCW) and the Judicial Commission of the Republik of Indonesia liaising East Java had implemented an anti-corruption movement with a focus on publik education and capacity building for youth and students and had exercised their authority and duties in realizing judges who were committed to implementing the Code of Ethics and the Judge's Conduct Guidelines (KEPPH) by monitoring special hearings on corruption cases.